2000
DOI: 10.1063/1.126281
|View full text |Cite
|
Sign up to set email alerts
|

Distributed feedback laser action from polymeric waveguides doped with oligo phenylene vinylene model compounds

Abstract: Articles you may be interested inLong-range surface plasmon single-mode laser concepts J. Appl. Phys. 112, 063115 (2012); 10.1063/1.4754417 Wafer-scale fabrication of polymer distributed feedback lasers

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2003
2003
2019
2019

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 37 publications
(11 citation statements)
references
References 10 publications
0
11
0
Order By: Relevance
“…18 Also, Kretsch et al demonstrated distributed feedback lasing from SP35 incorporated in a polystyrene waveguide. 19 Figure 1 shows the absorption cross-section spectrum of SP35 in ortho-xylene. The absorption crosssection of 10 -17 cm 2 at 355 nm is sufficiently large for the molecules to undergo population inversion when they are photoexcited by the third harmonic output of a Nd: YAG laser.…”
Section: Methodsmentioning
confidence: 99%
“…18 Also, Kretsch et al demonstrated distributed feedback lasing from SP35 incorporated in a polystyrene waveguide. 19 Figure 1 shows the absorption cross-section spectrum of SP35 in ortho-xylene. The absorption crosssection of 10 -17 cm 2 at 355 nm is sufficiently large for the molecules to undergo population inversion when they are photoexcited by the third harmonic output of a Nd: YAG laser.…”
Section: Methodsmentioning
confidence: 99%
“…Tuning is simply achieved by changing the angle between two interfering pump beams. Broad band tuning range has been demonstrated in several polymer materials using this configuration 4,5,6,7 . In this paper, we study and discuss by means of linear planar waveguide theory the modal content of the laser emission in DCM-dye doped PVK-polymer films 8 .…”
Section: Introductionmentioning
confidence: 95%
“…Broad band tuning range has been demonstrated in several polymer materials using this configuration [11][12][13]. In this paper, we study and discuss by means of linear planar waveguide theory the modal content of laser emission in DCM-dye-doped PVK-polymer films.…”
Section: Introductionmentioning
confidence: 98%